Translation of Diogenes Laërtius’ Vitae Philosophorum, Book IV: On the Academics - Brito, Rodrigo Pinto de; Dinucci, Aldo Lopes (Revista Archai, 2018)
Translation of Diogenes Laërtius’ Lives, book 4, dealing with the Academic thinkers after Plato.